Marilyn Monroe - Das geheimnisvolle Leben - Solt, Andrew; Remick, Lee
Lee Remick hosts this tribute to Marilyn Monroe, charting her rise to fame from her early years as struggling brunette photographer’s model to her later incarnation as a successful actress and blonde bombshell. [mubi.com]